2019
DOI: 10.1111/sjpe.12233
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal policy, government size and EMU business cycle synchronization

Abstract: We provide new evidence on the effects of fiscal policy and government size on pairwise business cycle synchronization in EMU. A novel time‐varying framework is employed to estimate business cycle synchronization and subsequently a panel approach is used to establish the role of fiscal variables in determining the pairwise synchronization observations across time. The findings suggest similarities in the size of the public sector, yet divergence in fiscal policy stance, matter for the determination of business… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…First, we focused on path dependence in business cycle co-movements, followed by economic integration and structure, and the impact of monetary and fiscal policies. Similar to Bunyan et al (2020) and Gächter and Riedl (2014), it can be observed that in all model specifications, current business cycle synchronicity positively depends on its last period. This is a logical path-dependent movement as the economic output not only addresses the current situation but also previous development.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…First, we focused on path dependence in business cycle co-movements, followed by economic integration and structure, and the impact of monetary and fiscal policies. Similar to Bunyan et al (2020) and Gächter and Riedl (2014), it can be observed that in all model specifications, current business cycle synchronicity positively depends on its last period. This is a logical path-dependent movement as the economic output not only addresses the current situation but also previous development.…”
Section: Resultsmentioning
confidence: 56%
“…We used the traditional Pearson correlation coefficient to measure the synchronization of business cycle development. For this purpose, we used seasonally adjusted quarterly data and extracted the cyclical component of GVA using Hodrick-Prescott (HP) and Christiano-Fitzgerald (CF) filters (Frankel & Rose, 1998;Darvas et al, 2005;Kunroo, 2019;Bunyan et al, 2020) . The final correlation coefficient was based on three-year forward-rolling windows.…”
Section: Resultsmentioning
confidence: 99%
“…Antonakakis and Tondl (2014) report significant results for fiscal policy coordination just in some specifications, while Sethapramote (2015) finds no statistically significant specification. Bunyan et al (2020) document significant results and establish a negative relationship between BCS and fiscal policy similarity. Beyond that, all other investigations used fiscal policy coordination as a control variable and the results presented in them are mixed.…”
Section: Literature Reviewmentioning
confidence: 89%
“…The third issue concerns problems associated with measurement. A measure of fiscal policy similarity based on differences in budget deficits is widely accepted in the literature (Beck, 2019; Böwer & Guillemineau, 2006; Bunyan et al., 2020; Duval et al., 2014; Furceri, 2009; Sachs & Schleer, 2013). However, measuring monetary policy similarity is more problematic, especially in the EU context, where a majority of the members are in the Eurozone.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation